2019
DOI: 10.3889/oamjms.2019.023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Treatment Results of the Thoracic Part of Oesophageal Cancer

Abstract: AIM:This study aims to evaluate the methods of treatment of the thoracic part of oesophagal cancer and to predict the results of treatment depending on the factors of the prognosis.MATERIALS AND METHODS:The results of treatment of 366 patients with cancer of the thoracic part of the oesophagus for 10 years (2007-2016) by the department of thoracic oncology of the Karaganda oncological dispensary were studied.RESULTS:The overall five-year survival rate, regardless of the method of treatment, was only 8.72% (28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The early symptoms of esophageal cancer are not obvious, and most patients are already in the middle and late stages when they are found. Because there are abundant large blood vessels and lymph nodes around the esophagus, its invasiveness is strong, and it has a high recurrence and metastasis rate, so the prognosis of esophageal cancer patients is poor and the survival rate is low, and its 5-year survival rate is 15-25%, which is one of the four major causes of in-hospital death in China [6][7][8]. Currently, the treatment of esophageal cancer is based on surgical resection as the main treatment method, combined with integrated treatment methods such as radiotherapy, chemotherapy, and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The early symptoms of esophageal cancer are not obvious, and most patients are already in the middle and late stages when they are found. Because there are abundant large blood vessels and lymph nodes around the esophagus, its invasiveness is strong, and it has a high recurrence and metastasis rate, so the prognosis of esophageal cancer patients is poor and the survival rate is low, and its 5-year survival rate is 15-25%, which is one of the four major causes of in-hospital death in China [6][7][8]. Currently, the treatment of esophageal cancer is based on surgical resection as the main treatment method, combined with integrated treatment methods such as radiotherapy, chemotherapy, and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The main treatments for EC are surgical resection, radiotherapy, and chemotherapy. Although great progress has been made in the treatment of EC, its prognosis is still poor, with a 5-year survival rate below 25% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies related to EC survival in recent years mainly focused on treatment methods including surgery [6], radiotherapy [7], and chemotherapy [8]. For instance, Spence et al [9] found that low-dose aspirin usage did not increase the survival of EC patients.…”
Section: Introductionmentioning
confidence: 99%